Molecular study of human metapneumovirus among children under 5 years with acute respiratory tract infection in Basrah city, Iraq - Noora Khudhur Abdulqader; Hazim Talib Thwiny; Aida A. Manthar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Human metapneumovirus (hMPV) is a major global factors that contributes to children getting acute respiratory tract infections (ARTI). This virus is frequently present in paediatric patients, with children under the age of two being particularly vulnerable. However,they are very common from early childhood until age five. Two hundred oropharyngeal swabs were collected from children with respiratory tract infections (RTIs), between December 2020 to December 2021 and were tested for hMPV. The database registered in the work included the sex, age, the season in which the specimen was obtained, feeding style, and the mother's education of infected children as well as major clinical respiratory tract infection symptoms. A molecular method was used to identify the presence of hMPV, and the results showed that 13% of the 200 samples tested positive for the virus. The samples were further broken down based on age groups, sex, season, feeding style, and mothers' education. According to age, the infection rate was noticed high in the age group (2-24 months) which was (13.7%) compared with (25-60 months) age group (12.4%) and there is no significant difference. The results were also shown according to the sex distribution, the infection with hMPV was more in males (14.8%) rather than females (9.7%). But this difference was not significant (P > 0.05). The majority of cases of hMPV occur in the winter and spring with a rate (15.8%), followedby (11.1%) in autumn. While 0 (0%) in summer. There was no noticeable difference (P > 0.05). The majority of hMPV infections have been identified with a rate (18.2%) in mixed feeding, followed by (13.0%) in bottle feeding and (10%) in breastfeeding. There was no significant difference (P > 0.05). while the distribution of infection hMPV against mother’s education was as follows: 13.2% in 7-12years and 12.9% in ≤6 years and 12.8% in ≥ 13 years.